Comparative analysis of sustainability indicators among the states of the Brazilian Amazon - Vale, Francinelli Angeli Francisco do; Toledo, Peter Mann de; Vieira, Ima Célia Guimarães (Sustainability in Debate, 2018)
In this paper, we elaborate a panorama of the sustainability for the nine states of the Legal Amazon, based on five dimensions, 13 themes and 54 indicators that form the Sustainable Development Index-SDI. Differences in states' levels of sustainability have been evidenced. Roraima was the only state with acceptable SDI performance, while Maranhão had the lowest score. The other states remained in the Alert range. The particularities and vulnerabilities of each state reflect the historical constraints, the geographical characteristics, and the development models adopted so far. SDI is considered to be a good optionforan evaluation tool because of its ability to address key sustainability issues and its methodological simplicity.